Penyembuhan Luka Diabetes dan Aktivitas Antimikroba dari Gel Ekstrak Melastoma malabathricum L. dan Psidium guajava L. pada Tikus Sprague Dawley - Refdanita Refdanita; Tonny Cortis Maigoda; Firdaus Firdaus; Barakatun Nisak; Teodhora Teodhora (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Diabetes mellitus (DM) is a degenerative disease characterized by abnormalities in carbohydrate, lipid, and protein metabolisms. This research was aimed at the gel’s pharmacological activity, the extract’s potential in treating diabetic wounds in male rats of Melastoma malabathricum L leaves (ML) and Psidium guajava L leaves (PL), as well as microbiological activity. Viscous extracts of ML and PL were prepared in gel dosage form with concentrations of 4% and 6%. Clindamycin was used as a positive control. This study was conducted using an experimental laboratory method, and the study population included white male rats. The pharmacological activity was tested in the form of a gel dosage formula, and the rats were made diabetic using alloxan. The potential of the extract was observed in healing diabetic wounds in male rats. ML and PL leaf extract gels affect wound healing in diabetic patients. This can be seen from the change in diameter. Wound swab examination revealed the presence of bacteria Klebsiella pneumoniae and Staphylococcus aureus. Secondary metabolites of flavonoids, tannins, steroids, and saponins help stimulate the regeneration of epithelial cells and tissues. The results for wound healing of 4% and 6% gel formulations were derived from maturation data on day 10.